Beyond drug-drug interactions: effects of transporter inhibition on endobiotics, nutrients and toxins. (3rd October 2017) - Lepist, Eve-Irene; Ray, Adrian S.
ABSTRACT: Introduction : Membrane transport proteins play a central role in regulating the disposition of endobiotics, dietary nutrients and environmental toxins. The inhibition of transporters by drugs has potential physiologic consequences. The full extent of the effect of drugs on the function of transporters is poorly understood because only a small subset of the hundreds of transporters expressed in humans – primarily those mediating the rate-determining step in the elimination of specific drugs – are assessed during clinical development. Areas covered : We provide a comprehensive overview of literature reports implicating the inhibition of transporters as the mechanism for off-target effects of drugs. Expert opinion : Transporter inhibition, the mechanism of action of many marketed drugs, appears to play an underappreciated role in a number of side effects including vitamin deficiency, edema, dyslipidemia, cholestasis and gout. Cell systems more broadly expressing transporter networks and methods like unbiased metabolomics should be incorporated into the screening paradigm to expand our understanding of the impact of drugs on the physiologic function of transporters and to allow for these effects to be taken into account in drug discovery and clinical practice.